Lignosulfonate-Based Adsorbents for Selective Mg2+ Removal from Mg2+/Li+ Mixture in Water with High Efficiency and Reusability - Paez-Collio, M; Paez-Collio, M; Oyarce-Riveros, E (Elsevier B.V., 2025)
This study focuses on the removal of Mg2+ from aqueous solutions during Li+ recovery. The objective was to capture Mg2+ ions by adsorption using based adsorbents of sulfonated lignin (LS) and poly-3-sulfopropyl potassium acrylate (PSPAK). The bio-based adsorbents were obtained in high mass yields by radical polymerization. Their structural composition and porous morphology were corroborated by infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). Lignin reinforces the mechanical properties of the material by increasing its toughness under a constant load, making it a suitable choice for adsorption processes. During the experiments, approximately 98.0 % of Mg2+ ions were removed using aqueous solutions with Mg2+/Li+ mass ratios (mg/L) of 0.5/1, significantly reducing the magnesium concentration in the aqueous medium. More than 90.0 % of Li+ was recovered from solution in the presence of Mg2+ at high ratios 8/1 and 10/1. The adsorbents retain their affinity for Mg2+ ions even in the presence of interfering ions such as Li+, Na+, K+, and Ca2+. Furthermore, they can be reused for more than five consecutive adsorption–desorption cycles, without a significant decrease in their adsorption efficiency and structural stability. The computational results indicate that the presence of Mg2+ ions has an impact on the stability and conformational behavior of the system. The polymer-Mg2+/Li+ system demonstrates a stronger affinity for Mg2+ compared to Li+. The increased adsorption energy and greater stability of the polymer-[Mg2+] combination provide evidence for the improved selectivity and effectiveness of polymer-based adsorbents in removing Mg2+ in the presence of Li+. © 2025 Elsevier B.V.